Trust Transfer in Social Commerce: The Role of Platform Trust and Seller Trust in Shaping Consumer Behavior in Indonesia - Dede Suleman; Wiwin Wianti; Devy Sofyanty; Raden Ati Haryati; Nurzalinar Joesah; Lukman Hakim (Dinasti Publisher, 2026)
This study aims to analyze the mechanism of trust transfer in social commerce in Indonesia by examining the influence of trust in the platform and trust in the seller on purchase intention. Based on Trust Transfer Theory, this study develops a model explaining how platform trust transfers to seller trust and influences purchase intention. Data were collected through a survey of 318 consumers who had transacted through social commerce platforms between December 2025 and January 2026. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares. The results show that trust in the platform has a positive and significant effect on trust in the seller. Trust in the seller is proven to be a major determinant of purchase intention and partially mediates the relationship between trust in the platform and purchase intention. The indirect effect through trust in the seller is greater than the direct effect of trust in the platform. These findings confirm that in Indonesian social commerce, the formation of interpersonal trust is a key mechanism linking institutional trust to purchasing behavior.